Dietary luteolin protects against renal anemia in mice. (February 2020) - Li, Siyu; Jiang, Huijie; Han, Bing; Kong, Tao; Lv, Yueying; Yang, Qingyue; Wu, Pengfei; Lv, Zhanjun; Zhang, Zhigang
Graphical abstract: Highlights: Luteolin relieves renal oxidative stress via activation of HIF-2α. Luteolin attenuates renal anemia via regulating the PHD2/HIF-2α axis. Luteolin may be a new drug for the treatment of renal anemia in future. Abstract: Luteolin (Lut) is a natural flavonoid with many biological activities which are ubiquitous in the diet. Renal anemia is a frequent complication of chronic kidney disease. However, the effect of Lut on renal anemia is not clear to date. This study firstly investigated the possible molecular mechanism that Lut protects against renal anemia in mice. Kunming mice received Lut (100 mg/kg) daily with or without mercuric chloride (HgCl2 ) exposure for 16 weeks. Mice from HgCl2 group displayed anemia, interestingly, Lut treatment alleviated it. The results of quantitative real-time PCR and western blot showed that Lut inhibited PHD2 in kidney, which is also confirmed by molecular docking study, and restored the expression of PHD2 downstream proteins, HIF-2α and erythropoietin. Furthermore, Lut suppressed renal oxidative stress via promoting the HIF-2α downstream antioxidant enzymes expression. Collectively, these findings demonstrate that Lut relieves renal anemia in mice via inhibiting PHD2/HIF-2α axis and oxidative stress.